KEPEMIMPINAN KEPALA SEKOLAH DALAM MENERAPKAN MANAJEMEN BERBASIS SEKOLAH UNTUK MENINGKATKAN KUALITAS PENDIDIKAN DI SMP MA’ARIF BATU - Syifaul Fauziyah; Muhammad Hanif; Fita Mustafida (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
Leadership is the school in implementing school-based management to improve the quality of education in SMP Ma’arif Batu. The purpose of this studi was to obtain a picture of the leadership of principals SMP Ma’arif Batu, school-based management SMP Ma’arif Batu, and the level of quality of education in SMP Ma’arif Batu, and knowing leadership is the school in implementing school-based management to improve the quality of education in SMP Ma’arif Batu. The data is obtained by means of observation,interview, and documentation. Of the analytical menthod used there are there stages namely data reduction data, presentation, and verification. The results of this study indicate that leadership is the school in implementing school-based management to improve the quality of education in SMP Ma’arif Batu has been going well, if seen the application of the principals in implementing school-based management to improve the quality of education, so that all probelms can be resolved and develop their potential. SMP Ma’arif Batu should pay more attention to leadership style and the application of school-based management not only responsible and participation in currriculum program programs and personnnel decisions but also responsible for increasing the accontability of program success. Principals must be smart in leading groups and delegating tasks and authority. So, that each group is awareof their respective duties and functions in applying the quality of education in SMP Ma’arif Batu.